Vous êtes sur la page 1sur 5

SOLUTION CHAPTER 2.

2
INTRODUCTION TO REAL ANALYSIS
BARTLE AND SHERBERT

Definition-: (Absolute value )

Absolute value of a real number ‘a’ is denoted by │a│ and is


defined as

-a if a≤ 0
│a│=
a if a ≥ 0
there are few properties of absolute value which can be proved
very easily here I’ll just write them I won’t prove them you can ask
me if you are not able to prove them you can mail me
sssshukla112@gmail.com

Property 1 Property 3

│a│= max{ a, -a} sqr(│a│) = sqr(a)=sqr(-a)

Property 2 Property 4

│a+ b│ ≤ │a│ + │b│ │a│ = │-a│

Now we have some basic idea about absolute value, we can now
solve the questions….
Geometrical meaning of│a│-:
│a│ is distance of real number ‘a’ from 0.

And │a- b│ is distance between ‘a’ and ‘b’

Q1(a)-: To show that │a│ =√ sqr(a)

Proof-:
Case 1 when a ≥ 0 we have on the L H S │a│= a
 sqr( │a│) = sqr(a)

 │a│ = √ sqr(a) (taking square root)


Case 2 a≤ 0 in that case we have │a│= -a
 sqr( │a│) = sqr(-a) = sqr(a)

 │a│ = √ sqr(a) (taking square root)

Q1(b)-:
│a/b│=│a│/│b│

Sqr (│a/b│) = sqr(a/b)

= sqr(a)/sqr(b)

= sqr( │a│)/ sqr( │b│)

= sqr(│a│/│b│)

=> │a/b│ = │a│/│b│ (taking +ve square root)

Q2 -:
│a+ b│ = │a│ + │b│ Iff ab ≥ 0

Proof-:

First let us assume that │a+ b│ = │a│ + │b│

To show that-: ab ≥ 0
As │a+ b│ = │a│ + │b│

 sqr(│a+ b│) = sqr(│a│ + │b│)

 sqr(a+b) = sqr(│a│) + sqr(│b│) +2│a││b│

 sqr(a)+sqr(b)+2ab= sqr(a)+sqr(b)+2│ab│

using facts that │a││b│=│ab│

and sqr(│a│) = sqr(a)

now using cancelation laws we have that


2ab=2│ab│
 ab=│ab│
 ab ≥ 0

conversely assume that ab ≥ 0

to show that -: │a+ b│ = │a│ + │b│

consider L H S

We have sqr(│a+ b│)=sqr(a+b)=sqr(a)+sqr(b)+2ab


( as sqr(│a│) = sqr(a) )

=> sqr(│a+ b│)=sqr(│a│)+sqr(│b│)+2│ab│

( as ab ≥ 0 therefore ab=│ab│)
=> sqr((│a+ b│)= sqr(│a│)+sqr(│b│)+2│a││b│

 sqr(│a+ b│)= sqr(│a│ + │b│)

 │a+ b│ = │a│ + │b│

(Taking +ve square root)

Q3 Given x,y,z in R with x≤ z, show that │x-y│+│y-z│=│x-z│iff


x≤ y≤ z

proof-:

firstly assume that x≤ y≤ z

to show that -: │x-y│+│y-z│=│x-z│

consider L H S

We have │x-y│= -x+y ( becoz x≤ y => │x-y│= -( x-y) )

Also │y-z│= -y+z ( becoz y≤ z =>│y-z│= -(y-z))

Therefore │x-y│+│y-z│= -x+y -y+z = z- x = │z-x│ (“ ,“ x≤ z)

=> │x-y│+│y-z│=│x-z│ (“ ,“ │a│ = │-a│)


Conversely assume that -:│x-y│+│y-z│=│x-z│……………(1)

To show that -: x≤ y≤ z

Now we have following possibilities

Case1 x-y ≤ 0 and y-z ≤ 0

Then L H S of (1) becomes -x+y -y+z = z-x = │x-z│= R H S of (1)

Therefore x-y ≤ 0 and y-z ≤ 0 is true => x ≤ y ≤ z


Now we’ll claim no other possibility is there.

Case2 x-y ≤ 0 and y-z ≥0

Then L H S of (1) becomes -x+y+y-z = 2y -x- z which is not equal


to R H S of (1)
Therefore this case is not possible

Similarlly you can check that other two cases are not possible too.

Q4 show that │x-a│<b <=> a-b < x < a+b

Proof-:

│x-a│<b <=>max{ -x+a , x-a}< b


<=> -x+a < b and x-a < b
<=> x> a – b and x < a+b
<=> a-b < x < a+b

SOLUTIONS PREPARED BY

SANJEEV KUMAR SHUKLA


MSc Mathematics(Delhi university)
Contact number-9718445143